A guide to solution‐based additive manufacturing of polymeric structures: Ink design, porosity manipulation, and printing strategy. Issue 1 (7th August 2019) - Zhang, Fengyi; Ma, Yao; Kondo, Yuzuki; Breedveld, Victor; Lively, Ryan P.
Abstract: Three‐dimensional (3D) printing of polymer solution is a rising research topic as it can utilize polymers without photoreactivity or melting points. Solution‐based additive manufacturing (SBAM) was recently reported to fabricate polymeric objects by depositing ternary polymeric inks (eg, solutions comprising polymer, volatile solvent, and nonvolatile nonsolvent), which undergo rapid phase inversion upon evaporation of a relatively small fraction of the volatile component, resulting in hierarchically porous filaments (eg, pores of diameters ranging from 2 nm to 10 μm). SBAM is conceptually compatible with any solution‐processable polymer, which significantly extends the 3D‐printable polymeric material spectrum. In addition to the architecture of the printed object, its internal porosity can be manipulated for different applications. Compared with typical direct ink writing of binary polymeric inks, which typically only contain the polymer and a volatile solvent, SBAM is capable of (a) eliminating evaporation‐induced shrinkage, and (b) creating nanopores without the need for templating additives or nanoscale nozzles. The development of SBAM processes involves optimization of polymer solution thermodynamics, rheological engineering and mass transfer control, which makes it challenging to develop an SBAM protocol for a new polymer. This paper provides a practical guide toward the development of ternary polymeric inks, the design of 3D printer hardware for SBAM, and the posttreatment of printed objects for desired porosity. It also discusses solutions to common challenges encountered during this new polymer processing technology. A case study of developing the optimal SBAM protocol for a commercial polyimide is provided to illustrate the process design.